PERENCANAAN DINAS PEKERJAAN UMUM DAN PENATAAN RUANG DALAM PENCEGAHAN BANJIR DI KOTA PEKANBARU TAHUN 2019 - Syarifah Vena Melinda; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The problem of flooding in Pekanbaru City is caused by river overflow due to obstruction of the flow of the Siak River to the sea caused by tides, causing an increase in the level of the Siak River. Meanwhile, those caused by rainfall are due to accumulated garbage and the amount of sand sediment in the drainage / drainage channel so that if there is rain the water flow will be hampered. Weather factors and the effects of climate change that trigger an erratic rainy season cannot be blamed but must be addressed by the government with adequate urban planning. Pekanbaru City Government does not have a Master Plan for flood prevention and water catchment areas for the long term. In addition, there is urban planning that reduces the absorption of water to the ground, such as semenising sidewalks. The formulation of this research is "How is the planning and what are the inhibiting factors of the Public Works and Spatial Planning Service in Flood Prevention in Pekanbaru City in 2019?" This study aims to analyze, identify and describe the planning and inhibiting factors of the Pekanbaru City Public Works and Spatial Planning Office in Flood Prevention in Pekanbaru City in 2019. This research is a descriptive type of research using a qualitative approach. Data collection techniques in this study using interview techniques, observation and documentation, data analysis used is qualitative analysis. The findings that can be concluded are the Planning of the Pekanbaru City Public Works and Spatial Planning Agency in 2019 in Flood Prevention through 5 stages of the development planning process: 1.Planning, there are obstacles such as not having a Flood Prevention Master Plan due to budget constraints so that the resolution of the flood problem is not optimal; 2. Programming, construction of sheet pile/talud/brojong, normalization of rivers and streams, and rehabilitation/maintenance of primary and secondary channels and bridges in flood prevention in Pekanbaru City; 3. Implementation of plans, the obstacles are not maximal implementation of programs and activities due to budget rationalization and not maximal drainage maintenance officers in carrying out their duties; 4. Supervision, supervises every program and activity carried out and reports any irregularities that occur and takes corrective action; 5. Evaluation, evaluating flood prevention development, one of the forms is a revidesign.  Keywords: Development Planning, Flood Prevention, Master Plan.